1997
DOI: 10.1152/ajpheart.1997.272.1.h567
|View full text |Cite
|
Sign up to set email alerts
|

Changes in myocardial blood volume with graded coronary stenosis

Abstract: Vasodilation of microvessels distal to a stenosis results in an increase in myocardial blood volume (MBV). The purpose of this study was to examine the changes in MBV induced by graded coronary artery stenoses by using myocardial contrast echocardiography (MCE). Accordingly, 21 dogs underwent progressive stenosis of a coronary artery in a random order, the severity of which was judged by the pressure distal to it. Total myocardial blood flow (MBF) to the bed distal to the artery (both anterograde and collatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 0 publications
7
48
0
Order By: Relevance
“…After allowance was made for the difference between arterial (0.4) and capillary Hct (0.3) in the dogs (28), the resting value of global MBV was measured as 0.064 mL/g, or 6.4%. This value is consistent with MBV measured with Chromium-51-labelled red blood cells in anesthetized dogs (29) and results of myocardial contrast echocardiographic techniques (30).…”
Section: Discussionsupporting
confidence: 88%
“…After allowance was made for the difference between arterial (0.4) and capillary Hct (0.3) in the dogs (28), the resting value of global MBV was measured as 0.064 mL/g, or 6.4%. This value is consistent with MBV measured with Chromium-51-labelled red blood cells in anesthetized dogs (29) and results of myocardial contrast echocardiographic techniques (30).…”
Section: Discussionsupporting
confidence: 88%
“…The increase of myocardial T 2 in response to hyperemia was significantly lower in the abnormally perfused territory than in normal myocar- dium. In contrast to severe stenosis (7), our dog model with moderate coronary artery stenosis showed little regional difference in the resting T 2 , which means that there is no regional difference in resting MBF (confirmed by the microsphere data), and the post-stenosis changes in MBV involving capillary recruitment were negligible with regard to this degree of stenosis (36,37). By the approximation of MPR, we observed that in remote myocardial regions the average values of MPR varied from two to four, while in the hypoperfused regions distal to stenosis a deficit MPR was consistently observed ranging from one to two.…”
Section: Discussionsupporting
confidence: 54%
“…2,21 If the sizes of the regions of interest and the ultrasound beam elevation are known, MBF can be calculated in absolute terms. Let us assume that a 1-cm 2 rectangular region of interest is placed over the myocardium and that the ultrasound beam elevation is 0.5 cm; therefore, the volume of tissue being examined is 0.5 cm 3 .…”
Section: Critique Of Our Methodsmentioning
confidence: 99%
“…A screw occluder was placed around the vessel to create coronary stenoses of various severities. 2 The severity of a stenosis was judged by the gradient between the central aortic and distal coronary pressure. Three stages were used: baseline and two different degrees of stenoses, which were not flow limiting at rest.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
See 1 more Smart Citation